Characterization of Streptococcus gordonii (S. sanguis) PK488 adhesin-mediated coaggregation with Actinomyces naeslundii PK606. - Kolenbrander, P E (1990)
Intergeneric coaggregation of Streptococcus gordonii (S. sanguis) PK488 and Actinomyces naeslundii PK606 was studied by using coaggregation-defective (Cog-) mutants of both strains. A streptococcal protein of 38 kilodaltons was identified with anti-S. gordonii serum absorbed with Cog- cells of the streptococcus. Absorbed immunoglobulin G specifically blocked coaggregation of the streptococcus-actinomyces pair but did not affect the coaggregation of the streptococcus with other coaggregation partners. The 38-kilodalton protein was found in the supernatant of mild sonicated cell suspensions and was extracted from whole cells with sodium barbital or with 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulfonate (CHAPS). An immunoreactive protein of the same size was found in sonicated cell supernatants of several other oral streptococci that also coaggregated with A. naeslundii PK606. Inhibition of S. gordonii PK488-A. naeslundii PK606 coaggregation was not observed with any of 16 different sugars tested. We propose that a functionally similar adhesin that mediates coaggregations with A. naeslundii PK606 is expressed by several species of the genus Streptococcus.